Evaluation of the Usefulness of Non-Test Instruments in Guidance and Counseling - Yona Apriliana; Nurfarhanah; Zadrian Ardi (Konsultan Jurnal Ilmiah Indonesia, 2025)
The urgency of improving the quality of Guidance and Counseling (BK) services demands accurate and holistic assessments, especially through the use of non-test instruments that are able to reveal students' affective, social, and psychological aspects. This study aims to analyze the effectiveness of non-test instruments in counseling services based on a literature study of 30 national and international journal articles. This research uses a descriptive qualitative method with a literature study approach, involving thematic analysis of publications from the last five years. The results show that non-test instruments, such as questionnaires, observations, interviews and sociometry, are effective in supporting a comprehensive understanding of students. However, their implementation still faces obstacles such as limited training and the lack of validated instruments. This study emphasizes the importance of strengthening the competence of counseling teachers and developing contextualized and standardized instruments. Future research is recommended to empirically evaluate the implementation of these instruments in schools.